Impact of OER-assisted Problem-based Learning on Creative Thinking and Self-Efficacy in Physics Education - Agung Sedayu; Herpratiwi Herpratiwi; Dwi Yulianti; I Wayan Distrik (Qubahan Academic Journal)
In the era of unlimited information, one method of learning is through the use of open education resources (OER) whereby It can be included into learning that is problem-based learning (PBL) to optimize students’ low creative thinking. This current study describes and investigates the impact of PBL with OER support on the acquisition and enhancement of secondary students’ creative thinking in the physics lesson viewed by the difference of self-efficacy. This study applied quasi-experiment research with pretest-post-test control group design in which 60 students in a public secondary school in Bandar Lampung were involved as the participant. Creative thinking test using physics content and self-efficacy questionnaire were administrated to students to collect the data. A few of statistical tests, such as: two ways ANOVA, paired t test, and independent t test whereby the software of SPSS v.26 was used to promote in analysing the data. Results found that there was a significant positive effect of the implementation of OER-assisted PBL on the acquisition and the enhancement of students’ creative thinking in physics lesson. Although the level of students’ self-efficacy has a significant role on the acquisition and enhancement of students’ creative thinking in physics learning but it is not depended on the learning model used either OER-assisted PBL or DI. Consequently, educational practitioners in the field of physics education, such as lecturer and teacher can implement PBL assisted by OER, such as e-book, e-module, web-based environment, etc., to optimize students’ creative thinking abilities or skills in which they can enhance their creative thinking, so getting the high achievement in physics subject. They also have to consider students’ self-efficacy level as one of the important factors in optimizing students’ creative thinking in physics learning.